Pengaruh Kinerja Usaha, Efisiensi Biaya Operasional, dan Keamanan Transaksi terhadap Kinerja Keuangan Coffee Shop di Kota Metro - Anas Izzulhaq, Muhammad; Zanaria, Yulita; Kurniawan, Angga (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to determine the influence of business performance, operational cost efficiency and transaction security on the financial performance of coffee shops in metro cities. The type of research used in this research is quantitative research. This research uses a sampling technique in the form of purposive sampling. This research uses primary data through questionnaires and the population in this study are the owners of Coffee Shops in Metro City, totaling 43 Coffee Shops. The data in this research were analyzed using the IMB SPSS 26 program. The results of this research show that Business Performance influences Financial Performance, Operational Cost Efficiency influences Financial Performance, and Transaction Security influences Financial Performance as well as Business Performance Compliance, Operational Cost Efficiency and Security. Simultaneous transactions affect the financial performance of coffee shops in Metro City.